Immersed in verse : an informative, slightly irreverent & totally tremendous guide to living the poet's life - Wolf, Allan (New York : Lark Books, 2006)
Contains advice, ideas, writing activities, and encouragement from a working poet for aspiring poets. Includes poems by a variety of poets from the unknown to the famous, including Langston Hughes, e.e. cummings, Eve Merriam, and more.
Includes bibliographical references (p. 110) and indexes.
Keywords: Poetry -- Authorship